Sistem Monitoring Konversi Wifi-RSSI Menjadi Jarak Antar Device dan Router Menggunakan Node-Red Pada Pengembangan Sistem Navigasi Dalam Ruang - Mubaroq, Rifqi Nafis; Aminah, Nina Siti (Proceedings Series on Physical & Formal Sciences, 2021)
A global positioning system (GPS) is often used as a tool for determining direction and positioning. However, GPS is weak in estimating the error, which is quite large at the actual distance, so positioning in a narrow area cannot work well. Therefore, a better method is needed to be used as a narrow-navigation system. This study aimed to determine whether RSSI has a better error than GPS for navigation devices in a narrow space or area. The method used was plotting graphs using Ms. Excel and determining the value of R square. The RSSI value was obtained through the Esp8266 device and then sent to the server via the MQTT protocol and converted using Node-Red on the Raspberry Pi. The comparison results of the Esp8266 device RSSI graph match the Laptop RSSI device as a reference. The match between the relative distance to the RSSI with the actual distance shows a 3.3-33% error. This result is considered much better than the GPS error.